Literacy Starts at Home in Early Childhood - Maleš, Dubravka (Array, 2007)
In the theoretical part of the paper, the emphasis is placed on discussing the impact of parental and family contexts on the development of a reading culture in young children as a prerequisite of the child’ s later performance. Indeed, the child’ s environment contributes significantly to the development of pre-reading skills as well as the child’ s motivation for independent reading. The empirical part of the paper contains some of the results obtained through a field survey conducted on a sample of 363 parents of pre-school children. The aim of the survey was to find out how many parents read to their pre-school children and how much importance the family attached to reading. Literacy is a skill that has to be mastered by each individual in contemporary society. It was believed for a long time that it was the teacher who affected the development of reading and writing skills the most, but the situation has turned out to be much more complex. (How to Help Every Child Become a Reader, 2001). The child’ s sensitivity to speech and language and his/her acquisition of knowledge required for the later use of speech and language depend on the environment from the child’ s earliest age. The sense of family and the communication that parents establish with the child from the day he/she was born have a key role in the development of reading skills.